Attenuating effect of lycopene and ellagic acid on 2,3,7,8-tetrachlorodibenzo-p-dioxin-induced spermiotoxicity and testicular apoptosis - Sönmez, M; Türk, G; Çeribaşı, Ao; Sakin, F; Ateşşahin, A (My University, 2011)
This study was conducted to investigate the prophylactic effects of lycopene (LC) and ellagic acid (EA) on 2,3,7,8- tetrachlorodibenzo-p-dioxin (TCDD)-induced testicular and spermatozoal toxicity. These toxicological changes are associated with the oxidative stress and apoptosis in male rats. Forty-eight male rats were allocated to one of six groups of 8 rats each: control, LC, EA, TCDD, TCDD+LC, and TCDD+EA. The control group was treated with 0.5 mL/ rat slightly alkaline solution+0.5 mL/rat corn oil every other day. The LC group was treated with 0.5 mL/rat slightly alkaline solution+0.5 mL/rat corn oil containing 10 mg/kg of LC every other day. The EA group received 0.5 mL/rat corn oil+0.5 mL/rat slightly alkaline solution containing 2 mg/kg of EA every other day. The TCDD group received 0.5 mL/rat corn oil containing 100 ng/kg/day of TCDD+0.5 mL/rat slightly alkaline solution. The TCDD+LC group was treated with 0.5 mL/rat TCDD+0.5 mL/rat LC. The TCDD+EA group was treated with 0.5 mL/rat TCDD+0.5 mL/rat EA. All treatments were made by gavage, and the experimental period was maintained during 8 weeks. Sperm motility, concentration, and abnormal sperm rate in epididymal tissue, testicular tissue lipid peroxidation (LPO), antioxidant enzyme activity, histopathological changes, and apoptosis (i.e., Bax and Bcl-2 proteins) were determined. TCDD exposure resulted in significant decreases in sperm motility, concentration, testicular superoxide dismutase activity, germinal cell-layer thickness, Johnsen’s testicular score, and significant increases in abnormal sperm rate, testicular malondialdehyde, glutathione levels, Bax-positive staining, and Bax-positive apoptotic cell score, along with some testicular histopathological lesions. TCDD treatment did not affect significantly catalase activity. However, combined treatment with LC or EA, in addition to TCDD, prevented the development of TCDD-induced damages in sperm quality, testicular histology, and LPO. Improvements in testicular apoptosis after the administration of LC and EA to TCDD-treated rats were minimal, but not statistically significant. TCDD-induced lipid peroxidation leads to functional and structural damages, as well as apoptosis, in spermatogenic cells of rats. Both LC and EA protected against the development of these effects
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Environmental pollutant; carotenoid; polyphenol; male reproduction; oxidative stress